A distributed location obfuscation method for online route planning. Issue 95 (August 2020) - Corcoran, Padraig; Mooney, Peter; Gagarin, Andrei
Abstract: A novel location obfuscation method for online route planning is proposed which is robust to privacy inferences by the service provider regarding route source and destination. This is achieved by performing the task of route computation in a distributed manner. Specifically, the client decomposes the required route into a sequence of shorter routes between intermediate locations. These routes are subsequently requested from independent online route planners with the results being integrated by the client to give the route originally required. Robustness to privacy inferences is a consequence of the fact that, without significant coordination and sharing of information, an individual online route planner cannot infer with high probability the true route source or destination. An evaluation of the proposed method is performed in the context of route planning within the street network of Boston. This evaluation demonstrates that the proposed method offers robustness to privacy inferences while exhibiting a reasonable reduction in quality of service.